45.0k views
3 votes
Let f(x)=6(2)x−1+4 .

The graph of f(x) is stretched vertically by a factor of 4 to form the graph of g(x) .

What is the equation of g(x) ?

2 Answers

2 votes
First simplify f(x)
f(x) = 6(2)x - 1 + 4
f(x) = 12x + 3
Then, multiply the slope by 4 to make it vertically stretched by a factor of 4.
g(x) = 4(12)x + 3
g(x) = 48x + 3
User Comet
by
4.8k points
4 votes

Answer:

24(2)^(x−1)+16

Explanation:

i just took the test

here is the correct answer v

Let f(x)=6(2)x−1+4 . The graph of f(x) is stretched vertically by a factor of 4 to-example-1
User Chris Trudeau
by
6.0k points